"2032 is a dream for us": exploring amputee football players` understanding of classification in para-sport and its application to amputee football - Engin, S. G.; Haegele, J. A.; Esatbeyoglu, F (Qualitative Research in Sport, Exercise and Health, 2025)
As amputee football rapidly gains popularity at the international level, it remains unrecognised by the International Paralympic Committee (IPC) due to the absence of a scientifically validated classification system. This presents a critical barrier to competitive equity within the wider para-sport landscape. This study explores amputee football players` perspectives on para-sport classification and their views on its potential implementation in amputee football. Using purposive sampling, twelve male amputee football players (11 outfield players, 1 goalkeeper; Mage = 28.2 ± 5.57; Mexperience = 8.4 ± 5.12 years) participated in semi-structured interviews. Data were analysed using Interpretative Phenomenological Analysis (IPA), enabling insights into how athletes interpret their lived experiences across contexts of performance, impairment, and legitimacy. In line with IPA`s idiographic commitment, each participant`s account was analysed individually before moving to cross-case analysis. After engaging with each participants` narrative, recurrent themes were identified, compared, and integrated across participants to reveal both convergences and divergences in experience. Findings were organised under four themes: the impact of amputation level on field performance; the meaning of acquired vs. congenital impairments; limited knowledge of para-sport classification; and reflections on its applicability to amputee football. The findings underscore that the development of an evidence-informed classification system must be grounded in athletes lived experience and embodied knowledge. By adopting a qualitative, phenomenological methodology, this study contributes to both the theoretical understanding of classification as a socio-phenomenological construct and offers actionable insight for classification policy in marginal para-sports.